Diseminasi Fertigator Otomatis Nirdaya untuk Budidaya Hortikultura di Kelompok Tani Saung Kiray, Kota Tasikmalaya - Budi Indra Setiawan; Riani Muharomah; Soni Trison; Ade Hilman Juhaeni (Institut Pertanian Bogor, 2026)
Unpowered Automatic Fertigator (FONi) is an automatic irrigation technology without the use of electrical power that has been proven to be able to provide water as well as dissolved nutrients directly to the root area according to plant needs (evapotranspiration). In this activity, FONi was introduced to the Saung Kiray Farmer Group (Mitra) of Tasikmalaya City for the cultivation of organic fruit and leaf vegetables in a neglected yard. The problem faced by Partners is the difficulty in watering plants which has been done manually and limited access to appropriate technology. This service aims to turn the abandoned yard into a productive one. By applying FONi, the yard can now produce various types of organic fruit and leaf vegetables that are beneficial for health and become a pilot and learning location, especially for the surrounding community. The students involved now have skills and experience in designing and making FONi and together with Partners have mastered its installation and use. Also produced, means of disseminating information on this service activity in the form of posters, videos and news and articles that can be a reference for the wider community. To ensure its sustainability, it is necessary to synergise with the Ministry of Agriculture's Sustainable Food Yard (P2L) programme and the local Agriculture Office, especially to support the National Free Nutritious Meal.